Blockchain Factors in the Design of Smart-Media for E-Healthcare Management - Dhaneshwar Shah; Sunanda Rani; Khadija Shoukat; Habiba Kalsoom; Muhammad Usman Shoukat; Hamad Almujibah; Shengxiao Liao (Sensors)
According to the current situation of deep aging globally, how to provide low-cost and high-quality medical services has become a problem that the whole society needs to consider. To address these challenges, we propose an e-healthcare management system leveraging the integration of the Internet of Things (IoT) and blockchain technologies. Our system aims to provide comprehensive, reliable, and secure one-stop services for patients. Specifically, we introduce a blockchain-based searchable encryption scheme for decentralized storage and real-time updates of electronic health records (EHRs). This approach ensures secure and efficient data traceability across medical equipment, drug supply chains, patient health monitoring, and medical big data management. By improving information processing capabilities, our system aspires to advance the digital transformation of e-healthcare services.